Analisis Tahapan Pengajaran Bilingual Bagi Siswa Sekolah Dasar di Indonesia - Dinda, Zuhria Qonita Naura; Ardinika, Salsabila Pratama Putri; Sari, Tiara Kartika; Nandini, Nadia Dwi; Citra, Deswita; Jayani, Sofiana Dewi; Widagdo, Arif (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
Bilingual teaching in elementary schools in Indonesia is increasingly important in the era of globalization, where mastery of more than one language is a much-needed skill. The stages of bilingual teaching consist of four stages: introduction, reinforcement, implementation, and consolidation. Each stage is designed to build students’ language skills gradually and systematically. Although bilingual teaching offers significant benefits, such as increased cognitive and academic achievement, its implementation still faces various challenges, including limited resources and teacher competence. This study uses a literature review method to evaluate the success of the bilingual program and find solutions to existing problems. It was found that student motivation, institutional support, and parental involvement are key factors in the success of bilingual teaching. This study also recommends strategies such as ongoing teacher training and the use of technology to improve the effectiveness of bilingual teaching in elementary schools.